Performance evaluation and benchmarking for the analytics era : 9th TPC Technology Conference, TPCTC 2017, Munich, Germany, August 28, 2017, Revised selected papers /: 9th TPC Technology Conference, TPCTC 2017, Munich, Germany, August 28, 2017, Revised selected papers. ([2018]) - Unknown
No abstract available